Phenolic Characterization and Quality Evaluation of Herbal Coffee from Roasted Juniper Berry Fruits (Juniperus drupacea L.): Elucidating the Impact of Roasting - Hasim Kelebek; Merve Carikcioglu; Pınar Kadiroglu; Esra Ereli; Turkan Uzlasir; Serkan Selli (Foods)
Consumers’ demand for foods with health benefits and different tastes is on an increasing trend. Juniper berries (“andiz” in Turkish) are the fruits of perennial, aromatic, and resinous Juniperus drupacea trees. In this study, quality properties of herbal coffee samples obtained from juniper berries roasted at three different temperatures (120, 160, and 200 °C) and four different durations (10, 25, 32.5, and 55 min) were elucidated. The herbal coffee samples were prepared from roasted and powdered fruits, and their total phenolic contents (TPCs), sugar profiles, antioxidant activities (AAs), and other quality parameters were examined. The highest AA value was determined as 17.99 and 29.36 mM Trolox/L (DPPH and ABTS, respectively) in the herbal coffee prepared from berries roasted at 120 °C for 25 min. Sucrose and glucose were dominant in all herbal coffee samples. Sixteen phenolic compounds were identified and quantified by a LC-ESI-MS/MS device. The TPC values of the herbal coffee varied from 236.7 to 917.0 g/L, and the procyanidin dimer, amentoflavone, methyl-biflavone, and digalloylquinic acid were dominant in all samples. The hydroxymethylfurfural (HMF) content of the herbal coffee varied between 0.01 and 0.39 mg/kg. According to a sensory analysis, the herbal coffee obtained from fruits roasted at 120 °C for 25 min was the most appreciated sample. In sum, this work shows that herbal coffee is non-caffeinated and is an alternative to regular coffee drinks derived from juniper berries roasted at lower temperatures and has more significant phenolic and antioxidant contents. It also has the potential to offer innovative and healthy alternatives to the food industry. Future research should focus on investigating how this herbal coffee can be positioned in the market and can influence consumer preference.